Cardiac tele-rehabilitation in times of pandemic. Experience at the National Cardiovascular Institute INCOR in Lima-Peru - Espinoza Pérez, Jessica (2023)
Objective. Cardiac Rehabilitation (CR) programs based on telehealth are an alternative in the context of a pandemic and represent an opportunity to continue in the intervention of cardiovascular diseases (CVD). The present study aims to evaluate the effect of a Cardiac Tele-Rehabilitation (CTR) program on quality of life, anxiety/depression index, exercise safety and Level Of disease awareness in patients discharged from a national referral institute in times of pandemic. Methods. A pre-experimental study in cardiac patients who entered the cardiac rehabilitation program at INCOR from August to December 2020. The study included low-risk patients who were administered a questionnaire (on cardiovascular disease, exercise safety, anxiety/depression, and quality of life) at the beginning and end of the program, which was applied through a virtual platform. Descriptive and comparative before-after analysis was used through hypothesis testing. Results. Sixty-four patients were included (71.9% male). The mean age was 63.6 ±11.1 years. Regarding exercise safety, an increase in the mean score was found after the application of the program (3.06 ± 0.8 to 3.18 ± 0.7, p=0.324). Concerning anxiety, the mean score was reduced from 8.61 to 4.75, while for depression, the reduction was from 7.27 to 2.92. Regarding the quality-of-life score, the global component improved from 111.48 to 127.92. Conclusions. The CTR program implemented through a virtual platform during the COVID-19 pandemic enhanced quality of life and decreased stress and depression in cardiac patients discharged from a national cardiovascular referral center.